Environment and home in Mahmoud Darwish’s poetry: an ecological perspective - Ruzy Suliza Hashim; Ahmed, Hamoud Yahya (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
Throughout the fifty years of the Palestinian poet Mahmoud Darwish’s writing life, home is a predominant theme in his poetry. In the authors’ reading of his work, the environment is closely linked to the notion of home and that is central to the field of ecocriticism that highlights the significance of environment to the study of literature. The discussion in this paper focuses on how Darwish represents ecology of home through the waves of his employment of environment in his homeland in his poetic production. His poems, which he writes from within his country and more keenly so when he is exiled from it, could be used to illustrate how an ecopostcolonial perspective might contribute to an understanding of the poet’s depiction of home through environment. To do this, the authors combined two theories -ecocriticism and postcolonial theory . by linking the marginality of environment in postcolonial theorizing with the centrism of environment in ecocriticism. The blending of the two theories illuminates how the ecological elements in his poems formulate the poet’s conception of home in the crisis-ridden modern world. As it has been shown, the poems of Darwish are populated with a continuous and unique development in the interaction between environment and home from the early poems to the poems of exile and the poems written upon returning home. In addition, Darwish definitely contributes to the facets of Palestinian environment and stirs up a sense of changing ecological notion of home in the Palestinian context. Thus Darwish’s use of nature becomes the basis of his agenda as a literary activist and shows how his identity is inseparable from the physical environment.